1983
DOI: 10.1152/ajprenal.1983.244.4.f355
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of glomerulotubular balance

Abstract: Glomerulotubular balance (GTB) is defined as the ability of each successive segment of the proximal tubule to reabsorb a constant fraction of glomerular filtrate and solutes delivered to it. For maintenance of GTB the coupling of peritubular blood flow and intratubular fluid flow to the process of glomerular filtration seems to be of functional importance since tubular fluid reabsorption is significantly altered when either or both parameters are experimentally changed. In the case of peritubular blood flow, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…This documented ability of the proximal tubule segments to adjust their transepithelial fluid transport in direct proportion to variations in SNGFR supports the contention (25) that glomerulotubular balance is closely maintained in remnant nephrons. Although in general the mechanisms governing glomerulotubular balance remain debatable, based on considerable investigative efforts it appears that peritubular (i.e., Starling forces) and luminal (i.e., intratubular volume flow and solute load) processes, which are in themselves usually linked to the filtered load, exert controlling influences on the maintenance ofglomerulotubular balance (26,27). Through the analysis ofthe relationship between APR and the reabsorptive determinants operating in the peritubular capillary environment of remnant nephrons, it is evident that LpAr could not contribute to increases in peritubular capillary fluid uptake.…”
Section: Discussionmentioning
confidence: 99%
“…This documented ability of the proximal tubule segments to adjust their transepithelial fluid transport in direct proportion to variations in SNGFR supports the contention (25) that glomerulotubular balance is closely maintained in remnant nephrons. Although in general the mechanisms governing glomerulotubular balance remain debatable, based on considerable investigative efforts it appears that peritubular (i.e., Starling forces) and luminal (i.e., intratubular volume flow and solute load) processes, which are in themselves usually linked to the filtered load, exert controlling influences on the maintenance ofglomerulotubular balance (26,27). Through the analysis ofthe relationship between APR and the reabsorptive determinants operating in the peritubular capillary environment of remnant nephrons, it is evident that LpAr could not contribute to increases in peritubular capillary fluid uptake.…”
Section: Discussionmentioning
confidence: 99%
“…However, the behaviour of the absolute rate of reabsorption in the two groups was opposite: it fell in parallel to SNGFR and inversely to PR in the sixty responders, while it rose slightly, albeit significantly, independent of SNGFR and parallel to PR in the non-responders. DISCUSSION Glomerulotubular balance represents the capacity of proximal volume absorption to follow closely the changes in filtration, so that the fraction of filtrate reclaimed proximally remains relatively constant (Bartoli, 1981;Haberle & von Baeyer, 1983). This property is important since it avoids an 'all-or-none' response to changes in filtration, that would end in anuria when GFR fell below the normal reabsorption rate.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these data indicate a peritubular mediation of GTB. In contrast, the perfusion of proximal tubular segments in vivo with plasma ultrafiltrate and with native tubular fluid (Haberle et al 1981;Haberle & Von Baeyer, 1983;Tucker & Blantz, 1978) suggested an additional mechanism for modulating proximal reabsorption by intraluminal flow rate per se. These studies were considered necessary after it was demonstrated that in vivo perfusion with artificial perfusates may depress reabsorption .…”
Section: Discussionmentioning
confidence: 96%